Composite plated part and method for manufacturing the same

By using silver plating solution with carbon particles added in the composite plating parts for electroplating and surface cleaning to remove some carbon particles, the problems of high carbon particles falling off and manufacturing cost are solved, and less carbon particles falling off and wear resistance are achieved effect.

CN114144544BActive Publication Date: 2024-12-17DOWA METALTECH CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202080053042.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-08-01
Filing Date
2020-06-04
Publication Date
2024-12-17
Estimated Expiration
2040-06-04

AI Technical Summary

Technical Problem

During pressurized processing, carbon particles are prone to fall off, dirtying the equipment or short circuit, and the manufacturing cost is high and the silver coating peeling may expose carbon particles, resulting in equipment contamination.

Method used

By electroplating using a silver plating solution with carbon particles added, a composite plating film composed of a composite material containing carbon particles in the silver layer is formed on the raw material, and ultrasonic or electrolytic cleaning removes part of the carbon particles on the surface to reduce the fall of carbon particles .

Benefits of technology

The composite plating parts produced have less carbon particles falling off and excellent wear resistance, which reduces the risk of equipment pollution and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003482751670000171
    Figure BDA0003482751670000171
  • Figure BDA0003482751670000181
    Figure BDA0003482751670000181
  • Figure BDA0003482751670000191
    Figure BDA0003482751670000191
Patent Text Reader

Abstract

The present invention provides a composite plated article having a composite plated film composed of a composite material containing carbon particles in a silver layer formed on a raw material and a method for manufacturing the same, wherein the carbon particles in the composite plated film are less likely to fall off. After the composite plated film composed of a composite material containing carbon particles in a silver layer is formed on a raw material (preferably composed of copper or a copper alloy) by electroplating using a silver plating solution to which carbon particles are added, a treatment is performed to remove a portion of the carbon particles on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a composite plated article and a method for producing the same, and in particular to a composite plated article used as a material for sliding contact parts such as switches and connectors and a method for producing the same. Background Art

[0002] Conventionally, as materials for sliding contact parts such as switches and connectors, silver-plated materials in which silver is plated on conductive materials such as copper or copper alloys are used in order to prevent oxidation of conductive materials such as copper or copper alloys due to heat during sliding.

[0003] However, silver plating is soft, easy to wear, and generally has a high friction coefficient, so there is a problem that it is easy to peel off due to sliding. In order to solve this problem, a method has been proposed in which carbon particles such as graphite or carbon black with excellent heat resistance, wear resistance, lubricity, etc. are electroplated on a conductor raw material to form a composite film in which graphite particles are dispersed in a silver matrix to improve wear resistance (for example, see patent document 1). In addition, a method has been proposed to manufacture a silver-plated film containing graphite particles by using a plating bath to which a wetting agent suitable for graphite particle dispersion is added (for example, see patent document 2). In addition, a method has been proposed to coat carbon particles with metal oxides or the like by a sol-gel method to improve the dispersibility of carbon particles in a composite plating solution of silver and carbon particles and increase the amount of composite carbon particles in the plating film (for example, see patent document 3).

[0004] However, the composite plated parts manufactured by the methods of Patent Documents 1 to 3 have a high friction coefficient and cannot correspond to the problem of extending the life of contacts or terminals. It is desired to provide a composite plated part that has a higher content of carbon particles and a higher proportion of carbon particles on the surface and has better wear resistance than the composite plated parts manufactured by the methods of Patent Documents 1 to 3.

[0005] As methods for producing such composite plated parts, the following methods have been proposed, among others: a method of forming a film composed of a composite material containing carbon particles in a silver layer on a raw material by electroplating using a cyanide silver plating solution to which oxidized carbon particles are added (see, for example, Patent Document 4); a method of forming a film composed of a composite material containing carbon particles in a silver layer on a raw material by electroplating using a composite plating solution obtained by adding carbon particles treated with a silane coupling agent after an oxidation treatment to a silver plating solution containing silver nitrate and ammonium nitrate (see, for example, Patent Document 5).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 9-7445 (Paragraph Nos. 0005-0007)

[0009] Patent Document 2: Japanese Patent Publication No. 5-505853 (pp. 1-2)

[0010] Patent Document 3: Japanese Patent Laid-Open No. 3-253598 (page 2)

[0011] Patent Document 4: Japanese Patent Application Publication No. 2006-37225 (Paragraph No. 0009)

[0012] Patent Document 5: Japanese Patent Application Publication No. 2007-262528 (Paragraph Nos. 0008-0009) Summary of the invention

[0013] Technical problem to be solved by the invention

[0014] However, when the composite plated part manufactured by the method of Patent Document 4 is used as a material for sliding contact parts such as switches or connectors, when the composite plated part is pressurized, there is a possibility that carbon particles on the surface will fall off and mix into the pressurized oil, thereby contaminating the equipment, or there is a possibility that the electronic equipment (using the sliding contact part, etc.) will short-circuit due to the detached carbon particles.

[0015] In addition, in the method of Patent Document 5, it is necessary to further form a silver-plated film on the composite-plated film of the composite-plated part, which increases the manufacturing cost. In addition, the silver-plated film formed on the composite-plated film may peel off, causing a short circuit in the electronic device. In addition, due to the peeling of the silver-plated film, it is possible that exposed carbon particles fall off and mix into the pressurized oil, thereby dirtying the equipment.

[0016] Therefore, in view of such existing problems, an object of the present invention is to provide a composite plated article having a composite plated film composed of a composite material containing carbon particles in a silver layer formed on a raw material and a method for manufacturing the same, wherein the carbon particles in the composite plated film are less likely to fall off.

[0017] Technical solutions adopted to solve technical problems

[0018] The inventors have conducted intensive research to solve the above-mentioned technical problems and have found that by using a silver plating solution to which carbon particles are added to perform electroplating, a composite plating film consisting of a composite material containing carbon particles in a silver layer is formed on a raw material, and then a treatment is performed to remove a portion of the carbon particles on the surface. This allows for the manufacture of a composite plated part having a composite plating film consisting of a composite material containing carbon particles in a silver layer formed on the raw material, wherein less carbon particles in the composite plating film fall off, thereby ultimately completing the present invention.

[0019] That is, the manufacturing method of the composite plated part of the present invention is characterized by performing electroplating using a silver plating solution to which carbon particles are added, forming a composite plated film composed of a composite material containing carbon particles in a silver layer on a raw material, and then performing a treatment to remove a portion of the carbon particles on the surface.

[0020] In the manufacturing method of the composite plated article, the treatment to remove a part of the carbon particles is preferably to perform ultrasonic cleaning or electrolytic cleaning on the surface of the composite plated film. In this case, the ultrasonic cleaning is preferably performed at 20 to 100 kHz for 1 to 300 seconds, and the electrolytic cleaning is preferably performed at 1 to 30 A / dm 2 The treatment is preferably performed for 10 to 300 seconds. In addition, the carbon particle removal rate based on the treatment of removing a portion of the carbon particles is preferably 20 to 75% by area, and the carbon particles are preferably graphite particles with an average particle size of 1 to 15 μm. In addition, the silver plating solution is preferably a sulfonic acid silver plating solution, and the amount of carbon particles added to the silver plating solution is preferably 10 to 100 g / L, and the electroplating is preferably performed at 0.5 to 10 A / dm 2 In addition, it is preferred that the raw material is made of copper or a copper alloy. In addition, it is preferred that a nickel plating film is formed on the raw material before forming a film made of the composite material.

[0021] In addition, the composite plated article of the present invention is characterized in that a composite plated film composed of a composite material containing carbon particles in a silver layer is formed on a raw material, the proportion of carbon particles on the surface of the composite plated film is 1 to 50% by area, and when an adhesive tape with an adhesive force of 4.02 N / 10 mm is attached to the surface of the composite plated film and then peeled off, the number of carbon particles attached to the adhesive tape is 35,000 pieces / mm 2 the following.

[0022] In the composite plated part, the thickness of the composite plated film is preferably 0.5 to 15 μm. In addition, the surface roughness Ra of the composite plated part is preferably 0.2 to 1.7 μm, and the friction coefficient is preferably 0.8 or less. In addition, a nickel plated film is preferably formed between the composite plated film and the raw material.

[0023] Furthermore, the terminal of the present invention is characterized by using the above-mentioned composite plated article as a material.

[0024] Effects of the Invention

[0025] According to the present invention, a composite plated article can be produced in which a composite plated film composed of a composite material including a silver layer and carbon particles is formed on a raw material, wherein the carbon particles in the composite plated film rarely fall off. DETAILED DESCRIPTION

[0026] In an embodiment of the method for manufacturing a composite plated part of the present invention, electroplating is performed using a silver plating solution to which carbon particles are added, and after a composite plated film consisting of a composite material containing carbon particles in a silver layer is formed on a raw material (preferably composed of copper or a copper alloy), a treatment is performed to remove a portion of the carbon particles on the surface.

[0027] In the manufacturing method of the composite plated part, as a treatment to remove a part of the carbon particles, ultrasonic cleaning, electrolytic cleaning, high pressure cleaning, polishing treatment and the like can be performed, but it is preferred to perform ultrasonic cleaning or electrolytic cleaning on the surface of the composite plated film. In the case of ultrasonic cleaning, it is preferably performed at 20 to 100 kHz for 1 to 300 seconds, and more preferably at 25 to 50 kHz for 2 to 270 seconds. In the case of electrolytic cleaning, it is preferably performed at 1 to 30 A / dm 2 10 to 300 seconds, more preferably 2 to 25 A / dm 2 The treatment is performed for 2 to 270 seconds. The carbon particle removal rate based on the treatment of removing a portion of the carbon particles on the surface is preferably 20 to 75% by area, more preferably 25 to 70% by area.

[0028] The carbon particles are preferably graphite particles, and the average particle size of the graphite particles is preferably 0.5 to 15 μm, more preferably 1 to 10 μm. In addition, it is preferred to remove the lipophilic organic matter adsorbed on the surface of the carbon particles by subjecting the carbon particles to an oxidation treatment. Such lipophilic organic matter includes aliphatic hydrocarbons such as alkanes and olefins, and aromatic hydrocarbons such as alkylbenzenes. As the oxidation treatment of the carbon particles, in addition to the wet oxidation treatment, an O-based 2Gas, etc., but from the perspective of mass production, wet oxidation treatment is preferably used, and wet oxidation treatment can be used to uniformly treat carbon particles with a large surface area. As a method for wet oxidation treatment, a method of adding an appropriate amount of oxidant after suspending the carbon particles in water can be used. As an oxidant, nitric acid, hydrogen peroxide, potassium permanganate, potassium persulfate, sodium perchlorate and other oxidants can be used. It is believed that the lipophilic organic matter attached to the carbon particles is oxidized by the added oxidant and becomes a form that is easily soluble in water, and is appropriately removed from the surface of the carbon particles. In addition, after the wet oxidation treatment, filtration is performed and the carbon particles are further washed with water, thereby further improving the effect of removing lipophilic organic matter from the surface of the carbon particles. By oxidizing the carbon particles, lipophilic organic matter such as aliphatic hydrocarbons and aromatic hydrocarbons can be removed from the surface of the carbon particles. According to the analysis of heating the gas at 300°C, the gas generated by heating the oxidized carbon particles at 300°C contains almost no lipophilic aliphatic hydrocarbons such as alkanes and olefins, and lipophilic aromatic hydrocarbons such as alkylbenzenes. Even if the carbon particles after oxidation treatment contain a small amount of aliphatic hydrocarbons or aromatic hydrocarbons, the carbon particles can be dispersed in the silver plating solution, but it is preferred that the carbon particles do not contain hydrocarbons with a molecular weight of more than 160, and the gas intensity (purge and trap gas chromatography-mass spectrometry intensity) generated by heating at 300°C with hydrocarbons with a molecular weight of less than 160 in the carbon particles is less than 5,000,000.

[0029] As the silver plating solution, a sulfonic acid-based silver plating solution is preferably used, which contains silver sulfonate as an Ag ion source and sulfonic acid as a complexing agent, and may also contain additives such as a brightener. The Ag concentration in the silver plating solution is preferably 5 to 150 g / L, more preferably 10 to 120 g / L, and most preferably 20 to 100 g / L. As the silver sulfonate contained in the sulfonic acid-based silver plating solution, silver methanesulfonate, silver alkanolsulfonate, silver phenolsulfonate, etc. can be used.

[0030] Furthermore, the amount of carbon particles added to the silver plating solution is preferably 10 to 100 g / L, more preferably 15 to 90 g / L, and most preferably 20 to 70 g / L. If the amount of carbon particles in the silver plating solution is less than 10 g / L, the content of carbon particles in the composite plated film may not be sufficiently increased, and even if it is greater than 100 g / L, the content of carbon particles in the composite plated film cannot be increased.

[0031] In addition, when forming the composite plated film, the electroplating is preferably carried out at a speed of 0.5 to 10 A / dm 2 The current density is preferably 1 to 5 A / dm 2 The current density is preferably 2 to 4 A / dm 2 If the Ag concentration or current density is too low, the formation of the composite plating film becomes slow and the efficiency is low. If the Ag concentration or current density is too high, the appearance of the composite plating film tends to be uneven.

[0032] As described in the embodiment of the method for manufacturing a composite plated part of the present invention, by using a silver plating solution to which carbon particles are added for electroplating, a film composed of a composite material in which carbon particles are dispersed in a silver layer is formed on a raw material, and a composite plated part having a large proportion of carbon particles on the surface and excellent wear resistance can be manufactured. In addition, by performing a treatment to remove a portion of carbon particles (carbon particles that are easy to fall off) on the surface of the film composed of the composite material (preferably performing an ultrasonic cleaning or electrolytic cleaning treatment on the surface of the composite plated film), a composite plated part in which a composite plated film composed of a composite material containing carbon particles in a silver layer is formed on the raw material can be manufactured, wherein the carbon particles in the composite plated film fall off less.

[0033] In addition, in an embodiment of the composite plated article of the present invention, in a composite plated article in which a composite plated film composed of a composite material containing carbon particles in a silver layer is formed on a raw material (preferably composed of copper or a copper alloy), the proportion of carbon particles on the surface of the composite plated film is 1 to 50 area %, and when an adhesive tape with an adhesive force of 4.02 N / 10 mm is attached to the surface of the composite plated film and then peeled off, the number of carbon particles attached to the adhesive tape is 35,000 pieces / mm 2 Below (preferably 10000 pieces / mm 2 If the proportion of carbon particles on the surface of the composite plated film is less than 1 area %, the wear resistance of the composite plated article is insufficient, and if it is greater than 50 area %, the contact resistance of the composite plated article increases.

[0034] The thickness of the composite plated film is preferably 0.5 to 15 μm, more preferably 1 to 10 μm, and most preferably 3 to 8 μm. If the thickness of the composite plated film is less than 0.5 μm, the wear resistance of the composite plated part is insufficient. If it is greater than 15 μm, the amount of silver increases and the manufacturing cost of the composite plated part increases. In addition, in order to improve the heat resistance of the composite plated part, a nickel plating film (preferably with a thickness of 0.5 to 5 μm) can also be formed between them. In addition, the surface roughness Ra of the composite plated part is preferably 0.2 to 1.7 μm, more preferably 0.2 to 1.3 μm. In addition, the friction coefficient of the composite plated part is preferably less than 0.8, more preferably less than 0.6, and most preferably 0.1 to 0.5.

[0035] In addition, two test pieces are cut out from the embodiment of the composite plated part of the present invention, one of the test pieces is used as a flat test piece (evaluation sample), and the other test piece is indented (hemispherical tumbling with inner R=1.0mm) to make a test piece with indentation (indenter), and a wear test is performed to confirm the wear state of the flat test piece by using a sliding wear tester, while pressing the test piece with indentation against the flat test piece with a certain weight (2N) and continuing the reciprocating sliding action (sliding distance 10mm, sliding speed 3mm / s) until the raw material is exposed. Preferably, when the wear resistance is evaluated, the raw material is not exposed after 500 reciprocating sliding actions. In addition, the force applied in the horizontal direction during the above-mentioned reciprocating sliding action is measured, and its average value F is calculated. When the dynamic friction coefficient (μ) between the flat test piece and the test piece with indentation is calculated according to μ=F / N, the dynamic friction coefficient is preferably 0.8 or less, and more preferably 0.6 or less.

[0036] Example

[0037] Hereinafter, embodiments of the composite plated article and the method for producing the same according to the present invention will be described in detail.

[0038] [Example 1]

[0039] As carbon particles, 6 wt% of flaky graphite particles with an average particle size of 5 μm were added to 3 L of pure water, and the mixed solution was stirred while heating to 50° C. Then, 1.2 L of a 0.1 mol / L potassium persulfate aqueous solution as an oxidant was slowly added dropwise to the mixed solution, stirred for 2 hours for oxidation treatment, and then filtered and separated with filter paper and washed with water.

[0040] The carbon particles before and after the oxidation treatment were analyzed by heating the gas at 300°C using a purge and trap gas chromatograph-mass spectrometer (Japan Analytical Industry JHS-100) (GCAS QP-5050A manufactured by Shimadzu Corporation). The results showed that the lipophilic aliphatic hydrocarbons (nonane, decane, 3-methyl-2-heptene, etc.) and lipophilic aromatic hydrocarbons (xylene, etc.) attached to the carbon particles were removed by the above-mentioned oxidation treatment.

[0041] In addition, as a raw material, a plate made of a Cu-Ni-Sn-P alloy (a copper alloy plate containing 1.0 mass % Ni, 0.9 mass % Sn and 0.05 mass % P, with the remainder being Cu) (NB109EH manufactured by Dowa Metal Co., Ltd.) with a thickness of 0.2 mm was prepared, and this raw material was used as a cathode, and a titanium platinum mesh electrode plate (platinum-plated titanium mesh raw material) was used as an anode, and a sulfonic acid-based Ag strike plating solution containing sulfonic acid as a complexing agent (DAIN Silver GPE-ST manufactured by Yamato Chemical Co., Ltd.) was used at a current density of 5 A / dm 2Electroplating (Ag strike plating) was performed for 30 seconds.

[0042] Furthermore, the carbon particles (graphite particles) subjected to the above oxidation treatment were added to a sulfonic acid-based silver plating solution having an Ag concentration of 30 g / L (DAIN Silver GPE-PL (matte) manufactured by Yamato Chemical Industry Co., Ltd.) containing sulfonic acid as a complexing agent, thereby preparing a sulfonic acid-based silver plating solution containing 30 g / L of carbon particles and 30 g / L of Ag.

[0043] Next, the raw material after the strike plating of Ag was used as a cathode, and the Ag electrode plate was used as an anode. The sulfonic acid silver plating solution to which the carbon particles were added was stirred at 500 rpm by a stirrer at a temperature of 25°C and a current density of 3 A / dm 2 Electroplating was performed for 250 seconds (current efficiency 95%), and a composite plating film (Ag-C plating film) containing carbon particles in the silver plating layer was formed on the raw material. The thickness of the composite plating film (1.0 mm diameter of the central part) was measured with a fluorescent X-ray film thickness meter (FT9450 manufactured by Hitachi High-Tech Sciences, Ltd.) and the result was 5.2 μm.

[0044] Next, the surface was partially cleaned by ultrasonic cleaning at 38 kHz for 5 seconds in pure water using an ultrasonic cleaner (USK-5 manufactured by Azwan Co., Ltd.), and then cleaned with pure water and dried with air flow to produce a composite plated product.

[0045] By observing the surface of the test piece cut out from the composite plated article thus obtained, the ratio of the area occupied by the carbon particles on the surface of the composite plated film (area ratio (area %)) was calculated. The surface of the test piece was irradiated with electron beams at an accelerating voltage of 5 kV using a desktop electron microscope (TM4000 Plus manufactured by Hitachi High-Tech Co., Ltd.), and the reflected electron composition (COMPO) image (magnification 1000 times) obtained from the reflected electron detector was binarized in grayscale (when the highest brightness of all pixels is set to 255 and the lowest brightness is set to 0, the pixels with brightness below 127 are black, and the pixels with brightness greater than 127 are white) using an image analysis application (image editing / processing software GIMP2.10.6), and separated into the silver part (white part) and the carbon particle part (black part), and the area ratio of the carbon particles on the surface of the composite plated film was calculated as the ratio Y / X of the number of pixels Y of the carbon particle part to the number of pixels X in the entire image. As a result, the area ratio (area ratio) occupied by the carbon particles on the surface of the composite plated film was 32 area %. In addition, for the composite plated part before the treatment of removing a portion of the carbon on the surface was performed, the area ratio (area rate) occupied by the carbon particles on the surface of the composite plated film was calculated by the same method, and the result was 64 area%, the change in the area rate based on the treatment of removing a portion of the carbon on the surface was 32 area% (=64 area%-32 area%), and the rate of change in the area rate (the removal rate of the carbon particles based on the treatment of removing a portion of the carbon on the surface) was 50 area% (=(64-32) area%×100 / 64 area%).

[0046] In addition, for the obtained composite plated parts, an image of the surface of the composite plated film taken at a magnification of 100 times using a laser microscope (VK-X1000 manufactured by Keyence Corporation) was analyzed using an analysis application (VK-HIXA, version 3.8.0.0 manufactured by KEYENCE Corporation), and the parameter representing the surface roughness (in the direction perpendicular to the rolling direction of the copper alloy plate material), namely, the arithmetic mean roughness Ra, was calculated in accordance with JIS B0601 (2001), and the result was 0.75 μm.

[0047] In addition, two test pieces were cut out from the composite plated part, one of which was used as a flat test piece (evaluation sample), and the other test piece was indented (hemispherical tumbling with an inner side R = 1.0 mm) to make a test piece with indentation (indenter). The test piece with indentation was pressed against the flat test piece with a certain weight (2N) using a sliding wear tester (manufactured by Yamazaki Seiki Laboratories, Ltd.), while continuing the reciprocating sliding action (sliding distance 10 mm, sliding speed 3 mm / s) until the raw material was exposed, and a wear test was conducted to confirm the wear state of the flat test piece. As a result, after 500 reciprocating sliding actions, the center of the sliding mark of the flat test piece was observed at a magnification of 200 times using a microscope (VHX-1000 manufactured by Keyence Corporation), and it was confirmed that the (brown) raw material was not exposed, indicating that the wear resistance was excellent. In addition, the force applied in the horizontal direction during the above-mentioned reciprocating sliding action was measured, and its average value F was calculated. The dynamic friction coefficient (μ) between the flat test piece and the test piece with indentation was calculated according to μ=F / N, and the result was that the dynamic friction coefficient was 0.24.

[0048] In addition, an adhesive tape (Cellotape (registered trademark) CT-18 (adhesion 4.02N / 10mm) manufactured by Nikki-Ban Co., Ltd.) was pasted on the surface of a sample piece cut out from the obtained composite plated part, and then the adhesive tape was peeled off to evaluate the adhesion of the composite plated film. The result showed that the composite plated film was not peeled off and the adhesion was good. In addition, the carbon particles attached to the peeled adhesive tape were observed at 1000 times using a laser microscope (VKX-160 manufactured by Keyence Corporation), and the carbon particles attached to the adhesive tape (carbon particles that fell off from the composite plated film) were counted. The result was 9600 pieces / mm 2 .

[0049] [Example 2]

[0050] A composite plated article was produced by the same method as in Example 1 except that the ultrasonic cleaning time was changed to 250 seconds.

[0051] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 26 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 64 area%, the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 38 area% (=64 area%-26 area%), and the change rate of the area rate was 59 area% (=(64-26) area%×100 / 64 area%).

[0052] In addition, the arithmetic mean roughness Ra of the obtained composite plated product was calculated by the same method as in Example 1 and the result was 0.55 μm.

[0053] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.52.

[0054] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 4800 pieces / mm 2 .

[0055] [Example 3]

[0056] The same raw materials as in Example 1 were used as cathodes and Ni electrode plates were used as anodes. In a nickel plating bath consisting of 80 g / L nickel sulfamate and 45 g / L boric acid, the solution temperature was 45°C and the current density was 4 A / dm 2 A composite plated article was produced by the same method as in Example 1 except that electroplating (Ni plating) was performed for 30 seconds while stirring at 40°C to form a 0.3 μm-thick Ni plating film on the raw material and then Ag strike plating was performed.

[0057] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 32 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 64 area%, and the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 32 area% (=64 area%-32 area%), and the change rate of the area rate was 50 area% (=(64-50) area%×100 / 64 area%).

[0058] In addition, the arithmetic mean roughness Ra of the obtained composite plated product was calculated by the same method as in Example 1 and the result was 0.75 μm.

[0059] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.24.

[0060] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 9600 pieces / mm 2 .

[0061] [Example 4]

[0062] A composite plated article was prepared by the same method as in Example 1, except that flaky graphite particles having an average particle size of 2 μm were used as carbon particles and the electroplating time during the formation of the composite plated film was changed to 25 seconds. The thickness of the composite plated film before the treatment of removing a portion of carbon from the surface of the composite plated article was measured by the same method as in Example 1 and the result was 0.5 μm.

[0063] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 2 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 5 area%, the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 3 area% (=5 area%-2 area%), and the change rate of the area rate was 60 area% (=(5-2) area%×100 / 5 area%).

[0064] In addition, the arithmetic mean roughness Ra of the obtained composite plated product was calculated by the same method as in Example 1 and the result was 0.23 μm.

[0065] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.13.

[0066] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 8400 pieces / mm 2 .

[0067] [Example 5]

[0068] A composite plated article was prepared by the same method as in Example 1, except that flaky graphite particles having an average particle size of 10 μm were used as carbon particles and the electroplating time during the formation of the composite plated film was changed to 500 seconds. The thickness of the composite plated film before the treatment of removing a portion of carbon from the surface of the composite plated article was measured by the same method as in Example 1 and the result was 10.6 μm.

[0069] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 34 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 62 area%, the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 28 area% (=62 area%-34 area%), and the change rate of the area rate was 45 area% (=(62-34) area%×100 / 62 area%).

[0070] In addition, the arithmetic mean roughness Ra of the obtained composite plated article was calculated by the same method as in Example 1 and the result was 1.28 μm.

[0071] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.47.

[0072] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off from the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off from the composite plated film were 7600 pieces / mm 2 .

[0073] [Example 6]

[0074] A composite plated article was produced by the same method as in Example 1 except that ultrasonic cleaning was performed at 28 kHz for 30 seconds using an ultrasonic cleaning machine (VS-100III manufactured by Azowan Co., Ltd.).

[0075] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 19 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 64 area%, the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 45 area% (=64 area%-19 area%), and the change rate of the area rate was 70 area% (=(64-19) area%×100 / 64 area%).

[0076] In addition, the arithmetic mean roughness Ra of the obtained composite plated product was calculated by the same method as in Example 1 and the result was 0.37 μm.

[0077] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.31.

[0078] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 3200 pieces / mm 2 .

[0079] [Example 7]

[0080] Instead of ultrasonic cleaning, an electrolyte solution containing 10% by mass of a cleaning rust inhibitor (BONDERITE C-AK PZ manufactured by Henkel Japan Co., Ltd.) dissolved in pure water (weakly alkaline liquid spray) was used, and an anode plate made of SUS304 and a raw material for forming a composite plating film were used as a cathode plate at 4 A / dm 2 A composite plated article was produced by the same method as in Example 1 except that electrolytic cleaning was performed for 30 seconds to remove a portion of carbon on the surface.

[0081] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 47 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 64 area%, the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 17 area% (=64 area%-47 area%), and the change rate of the area rate was 27 area% (=(64-47) area%×100 / 64 area%).

[0082] In addition, the arithmetic mean roughness Ra of the obtained composite plated product was calculated by the same method as in Example 1 and the result was 0.79 μm.

[0083] The obtained composite plated article was evaluated for wear resistance in the same manner as in Example 1. As a result, it was confirmed that the (brown) raw material was not exposed after 500 reciprocating sliding operations, indicating that the wear resistance was excellent.

[0084] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 28,000 / mm 2 .

[0085] [Example 8]

[0086] A composite plated article was produced by the same method as in Example 7 except that the electrolytic cleaning time was changed to 250 seconds.

[0087] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 44 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 64 area%, the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 20 area% (=64 area%-44 area%), and the change rate of the area rate was 31 area% (=(64-44) area%×100 / 64 area%).

[0088] In addition, the arithmetic mean roughness Ra of the obtained composite plated product was calculated by the same method as in Example 1 and the result was 0.72 μm.

[0089] The obtained composite plated article was evaluated for wear resistance in the same manner as in Example 1. As a result, it was confirmed that the (brown) raw material was not exposed after 500 reciprocating sliding operations, indicating that the wear resistance was excellent.

[0090] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 19600 pieces / mm 2 .

[0091] [Example 9]

[0092] In addition to 20A / dm2 A composite plated article was produced by the same method as in Example 7 except that electrolytic cleaning was performed.

[0093] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 43 area%, while the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 64 area%, and the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 21 area% (=64 area%-43 area%), and the change rate of the area rate was 33 area% (=(64-43) area%×100 / 64 area%).

[0094] In addition, the arithmetic mean roughness Ra of the obtained composite plated article was calculated by the same method as in Example 1 and the result was 0.74 μm.

[0095] The obtained composite plated article was evaluated for wear resistance in the same manner as in Example 1. As a result, it was confirmed that the (brown) raw material was not exposed after 500 reciprocating sliding operations, indicating that the wear resistance was excellent.

[0096] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 23600 pieces / mm 2 .

[0097] [Example 10]

[0098] In addition to 20A / dm 2 A composite plated article was produced by the same method as in Example 8 except that electrolytic cleaning was performed.

[0099] For the obtained composite plated article, the area ratio (area rate) of the carbon particles on the surface of the composite plated film was calculated by the same method as in Example 1. As a result, the area rate was 39 area%, the area rate of the composite plated article before the treatment of removing a portion of the carbon on the surface was 64 area%, the change in the area rate due to the treatment of removing a portion of the carbon on the surface was 25 area% (=64 area%-39 area%), and the change rate of the area rate was 39 area% (=(64-39) area%×100 / 64 area%).

[0100] In addition, the arithmetic mean roughness Ra of the obtained composite plated product was calculated by the same method as in Example 1 and the result was 0.63 μm.

[0101] The obtained composite plated product was evaluated for wear resistance in the same manner as in Example 1. The result showed that the arithmetic mean roughness Ra was 0.63 μm. Furthermore, after 500 reciprocating sliding operations, it was confirmed that the (brown) raw material was not exposed, indicating excellent wear resistance.

[0102] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 14,000 / mm 2 .

[0103] [Comparative Example 1]

[0104] A composite plated article was produced by the same method as in Example 1 except that the treatment for removing part of the carbon on the surface was not performed.

[0105] The arithmetic mean roughness Ra of the obtained composite plated article was calculated by the same method as in Example 1 and the result was 1.78 μm.

[0106] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.19.

[0107] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 51200 pieces / mm 2 .

[0108] [Comparative Example 2]

[0109] A composite plated article was produced by the same method as in Example 4 except that the treatment for removing part of the carbon on the surface was not performed.

[0110] The arithmetic mean roughness Ra of the obtained composite plated article was calculated by the same method as in Example 1 and the result was 0.34 μm.

[0111] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.12.

[0112] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the composite plated film did not peel off and the adhesion was good. In addition, the carbon particles falling off the composite plated film were 35600 pieces / mm 2 .

[0113] [Comparative Example 3]

[0114] After the composite plated film was formed, a silver plated film was formed on the composite plated film, and a treatment for removing part of the carbon on the surface was not performed. A composite plated article was produced in the same manner as in Example 1. In addition, a sulfonic acid-based silver plating solution (DAIN Silver GPE-PL (matte) manufactured by Yamato Chemical Industry Co., Ltd.) with an Ag concentration of 30 g / L and containing sulfonic acid as a complexing agent was used. The solution temperature was 25° C. and the current density was 3 A / dm 2 The electroplating was performed for 60 seconds to form a silver plated film.

[0115] The area ratio (area ratio) of the carbon particles on the surface of the composite plated film was calculated for the obtained composite plated article by the same method as in Example 1. The result was that the area ratio was 36 area %, and the area ratio after the silver plated film was formed was 64 area %.

[0116] In addition, the arithmetic mean roughness Ra of the obtained composite plated article was calculated by the same method as in Example 1 and the result was 0.76 μm.

[0117] In addition, the wear resistance of the obtained composite plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 500 reciprocating sliding actions, it was confirmed that the (brown) raw material was not exposed, which shows that the wear resistance is excellent. In addition, the dynamic friction coefficient is 0.19.

[0118] In addition, the adhesion of the composite plated film was evaluated by the same method as in Example 1, and the carbon particles falling off the composite plated film were counted. As a result, the silver plated film formed on the composite plated film peeled off and the adhesion was poor. In addition, the carbon particles falling off from the composite plated film were 21200 pieces / mm 2 .

[0119] [Comparative Example 4]

[0120] A silver-plated article was produced in the same manner as in Example 1 except that a silver-plated film was formed instead of a composite-plated film and that a treatment for removing part of the carbon on the surface was not performed. In addition, a sulfonic acid-based silver plating solution (DAIN Silver GPE-PL (matte) manufactured by Yamato Chemical Industry Co., Ltd.) with an Ag concentration of 30 g / L and containing sulfonic acid as a complexing agent was used, and the reaction mixture was heated to 25° C. and a current density of 3 A / dm 2 The electroplating was performed for 250 seconds to form a silver plated film. The thickness of the silver plated film of the silver plated article was measured by the same method as in Example 1 and found to be 5.6 μm.

[0121] The arithmetic mean roughness Ra of the obtained silver-plated product was calculated by the same method as in Example 1 and the result was 0.19 μm.

[0122] In addition, the wear resistance of the obtained silver-plated part was evaluated and the dynamic friction coefficient was calculated by the same method as in Example 1. As a result, after 57 reciprocating sliding actions, the (brown) raw material was confirmed to be exposed, and it was found that the wear resistance was not good. In addition, the dynamic friction coefficient was 1.85.

[0123] The obtained silver-plated article was evaluated for adhesion of the silver-plated film by the same method as in Example 1. As a result, the silver-plated film was not peeled off and the adhesion was good.

[0124] [Comparative Example 5]

[0125] In addition to the current density of 3A / dm 2 The silver-plated article was prepared by the same method as in Example 1 except that Ag strike plating was performed for 10 seconds to form an antimony-containing silver plating film instead of the composite plating film, and no treatment was performed to remove part of the carbon on the surface. The antimony-containing silver plating film was formed by using an antimony-containing silver plating solution (manufactured by Nikken Chemicals Co., Ltd.) at a liquid temperature of 25°C and a current density of 1 A / dm 2 The electroplating was performed for 400 seconds. The thickness of the silver plated film of the silver plated article was measured by the same method as in Example 1 and found to be 5.3 μm.

[0126] The arithmetic mean roughness Ra of the obtained silver-plated product was calculated by the same method as in Example 1 and the result was 0.10 μm.

[0127] In addition, the wear resistance of the obtained silver-plated part was evaluated by the same method as in Example 1, and the dynamic friction coefficient was calculated. As a result, after 370 reciprocating sliding actions, the (brown) raw material was confirmed to be exposed, and it was found that the wear resistance was not good. In addition, the dynamic friction coefficient was 0.82.

[0128] The obtained silver-plated article was evaluated for adhesion of the silver-plated film by the same method as in Example 1. As a result, the silver-plated film was not peeled off and the adhesion was good.

[0129] The production conditions and properties of the plated articles of these Examples and Comparative Examples are shown in Tables 1 to 3. In Table 3, good adhesion of the plated film is indicated by ○, and poor adhesion is indicated by ×.

[0130] [Table 1]

[0131]

[0132] [Table 2]

[0133]

[0134] [Table 3]

[0135]

Claims

1. A method for manufacturing a composite plated part, characterized in that: After electroplating with a silver plating solution containing carbon particles, a composite plating film consisting of a composite material in which carbon particles are dispersed in a silver layer is formed on the raw material, and then the surface of the composite plating film is ultrasonically cleaned at 38 to 100 kHz for 1 to 300 seconds or at 1 to 30 A / dm 2 Electrolytic cleaning is performed for 10 to 300 seconds to remove part of the carbon particles on the surface.

2. The method for manufacturing a composite plated article according to claim 1, characterized in that: The carbon particle removal rate based on the treatment of removing the part of the carbon particles is 20 to 75 area %.

3. The method for manufacturing a composite plated article according to claim 1, characterized in that: The carbon particles are graphite particles with an average particle size of 1 to 15 μm.

4. The method for manufacturing a composite plated article according to claim 1, characterized in that: The silver plating solution is a sulfonic acid silver plating solution.

5. The method for manufacturing a composite plated article according to claim 1, characterized in that: The amount of carbon particles added to the silver plating solution is 10-100 g / L.

6. The method for manufacturing a composite plated article according to claim 1, characterized in that: The electroplating temperature is 0.5 to 10 A / dm 2 The current density is carried out.

7. The method for manufacturing a composite plated article according to claim 1, characterized in that: The raw material is formed of copper or a copper alloy.

8. The method for manufacturing a composite plated article according to claim 1, characterized in that: Before forming the film composed of the composite material, a nickel plating film is formed on the raw material.

9. A composite plated part, characterized in that: A composite plated film consisting of a composite material in which carbon particles are dispersed in a silver layer is formed on a raw material, wherein the proportion of carbon particles on the surface of the composite plated film is 1 to 50% by area, the surface roughness Ra of the composite plated film is 0.2 to 1.7 μm, and when an adhesive tape having an adhesive force of 4.02 N / 10 mm is adhered to the surface of the composite plated film and then peeled off, the number of carbon particles attached to the adhesive tape is 35,000 / mm 2 the following.

10. The composite plated article according to claim 9, characterized in that: The thickness of the composite coating film is 0.5-15 μm.

11. The composite plated article according to claim 9, characterized in that: The friction coefficient of the composite plated part is less than 0.

8.

12. The composite plated article according to claim 9, characterized in that: A nickel plating film is formed between the composite plating film and the raw material.

13. A terminal, characterized in that The composite plated article according to claim 9 is used as a material.

Citation Information

Patent Citations

  • Dispersion plating method

    JP1991253598A

  • Method for forming silver-graphite dispersion coating

    JP1993505853A

  • Sliding contact of electric equipment

    JP1997007445A

  • Composite plated material and method for producing same

    JP2006037225A

  • Method of manufacturing composite plated material

    JP2007262528A